Specific Features Of The Term Formation In English (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the specific linguistic and structural features of term formation in English. As terminology serves as the cornerstone of scientific and technical communication, understanding how terms are created, adapted, and standardized is vital across disciplines. This study examines the morphological, syntactic, and semantic mechanisms involved in English term formation, analyzes trends such as borrowing, compounding, and affixation, and highlights how technological innovation and globalization influence terminological development. The findings demonstrate that term formation in English is dynamic, systematic, and increasingly influenced by interdisciplinary and intercultural factors.